A sociological Analysis on the Modes of Science Production - Ali Rabbani Khorasgani; Vahid Ghasemi; Rasol Rabbani; Mehdi Adibi Sadeh; Nader Ofoghi (Taḥqīqāt-i Farhangī-i Īrān)
The main aim of this article was sociological Analysis on the modes of science, survey of new Approaches in this context, description of available Approaches relevant to Application of Indigenous paradigm in prodvetion of knowledge and conclusion to attain imitated Approaches from Analysis and mentioned discussions for planning in space of science production in society of Iran. After Analysis of propound Approaches in sociology of science concreted that sociology of science three generation transitioned yet : classic sociology of science (OSS) [ Theories of Merton ] , New sociology of science ( NSS ) [Theories of Thomas kuhn and others ] and Third generation sociology of science that consisted of non - Marxist composinal and processive Approaches for example: Actor - Network theory (ANT), Triple Helix Theory life eyeles, mode 2 and Mode 3. On the other hand , because science production is encompass process in social structures and social communications , allowance for Analysis of Recent Development in mode of science production , three paradigm Analysis and critiqued titles mode 1 , 2 , 3 production of knowledge . Also, Application of Indigenous paradigm studied in production of knowledge and introduced two groups: A - External Approaches B - Internal Approaches that each of two groups propounded Ideas relevant to Indigenous knowledge and Indigenization of knowledge. In the final section, mode an efforted to answered this question that what doctrines can be concluded from these discourse in order to improve the conditions in Iran.